The effect of separating layer between reacting media and molding template on the porous structure of combustion synthesized Ni-Al intermetallics - Pichugin, Nikita; Kirdyashkin, A.; Kitler, V. D.; Maznoy, Anatoly (Materials letters)
This research focuses on identifying conditions under which porous intermetallics with a welded granular structure comprised of mm-sized spheroidal alloy elements can be directly obtained by combustion synthesis using mu m-sized metal powders as starting reagents. The heat loss of reacting medium to a molding template used to shape a powder mixture of reagents significantly reduce the size of the alloy elements in manufactured material, especially near the mixture/template interface. One possible solution to this problem is to employ a separating layer between the powder mixture and the molding template. The effect of separating layers, both chemically inert (ceramic-based) and active (cellulose-based), on the size of Ni-Al elements has been experimentally studied. It was found that notable structure modification can be achieved by using cellulose-based separating layers. The carbon-containing products released during cellulose pyrolysis interact with the reacting medium and promote the coalescence of metal melts. Changing the thickness of the cellulose-based separating layer is an easy way to control the porous structure and permeation properties of combustion synthesized Ni-Al-based intermetallics, which makes them relevant for practical application.